A comunidade na escola: limites e possibilidades para a participação dos pais no conselho de escola e na associação de pais e mestres - Matsui, Lucia Mieko (2006)
This aim of this study was to understand the role of the School Council and the teachers and parents Association as channels for the parent participation in the school policy. The aim of this empirical research based in the date comprehended by official documents, question forms and personal interviews that they are obtained from the principals, teachers and student parent of the far state schools in the city of Guarulhos (SP). This result shows that parent participation is incipient and that there are internal and external (related to school) factors that impede their participation. The author conclude that the School Council and Teachers and Parents Association that they use this means as a way of an important channel for communication between school as institution and parents.